Profiling cases of gangsterism in school in Malaysia - Boon, Yusof; Yahaya, Azizi; Hashim, Shahrin; Ujang, Rosnah (Faculty of Education, 2008)
The purpose of the study is to identify the main factors wihch influences secondary students in the gangsterisme social activity focused in four states such as in Johore, Malacca, Negeri Sembilan and Selangor. In the research 400 from 4 students were chosen. The data were collected using questionnaire which was adopted from Gangs Acitivities Perception Questionnaire (FAPQ) dan Perceptions Toward Youth Gangs. The alpa croncbach for this instrument was 0.8432. Students reported that overall rate on the gengsterisme prevalance were at moderate level at low level. When having problems about gengsterisme, friends were the most influences refered to by the students compared family. The findings also indicated that there were no significant correlations between factors which influences secondary students in the gangsterisme social acitivity with the academic achievement and family income. The level of factors which influences secondary students in the gangsterisme social acitivity was found as low level.